Interface between child education and special education: studies on child care in current (Revista Educação, Artes e Inclusão, 2021)
This study aimed to identify research in master's and doctoral programs related to the interface between Early Childhood Education and Special Education. A brief overview of Early Childhood Education and Special Education was presented in its legal aspects and in terms of teacher education. From the bibliometric procedure, we verified the amount of work, year of its defense and level (master's degree or doctorate degree). For the search we used the descriptors: “Early Childhood Education” AND “Special Education”, for the database of the Thesis and Dissertation Catalog of the Higher Education Personnel Improvement Coordination, there was refinement of the research in the large area of ​​knowledge: Humanities. Totaling the corpus of this work with a total of 13 theses and 45 dissertations. There was a temporal distribution of scientific productions from 2004 to 2019, as well as by regions of the country with the highest concentration in the Southeast followed by the South; due to administrative dependence, most of the scientific production was carried out at HEIs at the Federal level; the Postgraduate Programs with research within the interface were divided into three areas: Education, Special Education and School Education and the population of registered coverage was the majority on disabilities in general followed by intellectual disabilities and a smaller number on the other disabilities.
Keywords: special education; child education; inclusive education